Big 5 personality traits as the predictors of psychological well-being adults working from home (WFH) in Malaysia during COVID-19 pandemic - Liew, Qian Qi; Lim, Yee Wen (2022)
Psychological well-being plays an imperative role in each working adults’ lives, especially during the pandemic of COVID-19. However, there are many working adults turned up to have low psychological well-being when facing the huge transaction caused by the pandemic. Thus, the present study aims to focus on how personality traits affect psychological well-being among adults Working From Home (WFH) in Malaysia during the COVID-19 pandemic. This cross-sectional study applied a quantitative survey method were applied in the present study in order to test the hypotheses. Purposive and snowball sampling methods were used to recruit participants and the questionnaire was mainly distributed through social media. Demographic information, Big Five Inventory (BFI) and Ryff’s Psychological Well-Being (RPWB) were included in the questionnaire. There were 112 adults working from home in Malaysia who participated in the present study after filtering out those who were not eligible and disagree to proceed with their personal data. The finding showed that openness, conscientiousness, extraversion and agreeableness were significantly and positively correlated with psychological well-being, while neuroticism was significantly and negatively correlated with psychological well-being. Additionally, except for openness, all of the personalities were significantly predicted psychological well-being. The present study makes a significant contribution to the literature and increase the knowledge of the relationship between personality traits and psychological well-being among working adults in Malaysia and let the employees understand how their personality traits of the employees will affect their job performances if their psychological well-being is unstable.